French crime fiction and the Second World War : Past crimes, present memories. - Gorrara, Claire (Cultural history of modern war., 2017)
By investigating representations of the war years in a selection of French crime novels from the mid-1940s to the present day, this book argues for the importance of crime fiction, and popular culture more generally, as active agents of memory in the ongoing debates over the legacies of the war years in contemporary France.